Characteristics of patients with body mass index recorded within the Kent Integrated Dataset (KID) - Zara Cuccu; Gerrard Abi-Aad; Allison Duggal (BMJ Health & Care Informatics)
Background Obesity is a significant health issue and key public health priority. This study explored body mass index (BMI) recording in general practice within the Kent Integrated Dataset.Methods Using a sample aged 18–100 years, resident within Kent, who were alive and currently registered to a Kent general practice as of 6 August 2018 within the Kent Integrated Dataset. We identified the latest BMI from event records between 2015/2016 and 2017/2018. Recording was evaluated by sex, age, deprivation, hypertension, serious mental illness and multimorbidity.Results Between 2015/2016 and 2017/2018 using the sample of 1 154 652 persons, BMI was recorded for 43.7% of the sample. Multiple logistic regression showed that BMI recording was higher in females, the middle age bands, persons living in the most deprived areas and within persons who were hypertensive, had serious mental illness or were multimorbid.Conclusions Findings were aligned to previous research using nationally representative samples. Completeness of recording varied by age, sex, deprivation and comorbidity. Recording within general practice was aligned to chronic disease management. From a prevention perspective, earlier assessment and intervention for the management of excess weight within primary care may be an opportunity for avoiding increases in BMI trajectory. There may also be merit in recognising that the external disease agents that influence obesity can be controlled or reduced (obesogenic environment) from a national policy perspective. Such a perspective may also help reduce stigmatisation and the pressure around arguments that centre on personal responsibility for obesity.